Raised pro-inflammatory cytokines interleukin 6 and tumour necrosis factor alpha in coeliac disease mucosa detected by immunohistochemistry. Issue 10 (October 1994) - Przemioslo, R T; Kontakou, M; Nobili, V; Ciclitira, P J
Abstract : The levels of two pro-inflammatory cytokines, interleukin 6 (IL-6) and tumour necrosis factor alpha (TNF-alpha), in coeliac disease were studied by immunohistochemistry. Jejunal biopsy specimens from patients with untreated disease, (n = 11), treated disease (n = 9), and normal controls, (n = 11) were stained to detect IL-6, TNF-alpha, CD45 (pan-leukocyte), and CD68 (macrophage surface antigen). Positive cells were identified in the epithelium (per 100 enterocytes) and in the lamina propria (per unit area). There was a significant increase in median IL-6 and TNF-alpha staining in both the lamina propria and the epithelium of untreated coeliac disease patients (lamina propria, 16.2 and 13.0 respectively; epithelium, 0.86 and 1.21, all p < 0.05) when compared with treated coeliac disease patients (lamina propria; 6.0 and 6.2, epithelium; 0.60 and 0.60) and controls (lamina propria; 6.5 and 7.5, epithelium; 0.58 and 0.60). A significant increase in the number of CD45 positive cells was found in the untreated coeliac disease lamina propria and epithelium (p < 0.05) but this was accompanied by a significant rise in CD68 positive cells in the lamina propria only (p < 0.05). Increased IL-6 and TNF-alpha in the lamina propria and epithelium of patients with untreated coeliac disease further supports their role in the immune pathogenesis of this disorder.